An assay for evoked locomotor behavior in Drosophila reveals a role for integrins in ethanol sensitivity and rapid ethanol tolerance. - Bhandari, P.; Kendler, K.S.; Bettinger, J.C.; Davies, A.G.; Grotewiel, M. (Alcoholism, Clinical and Experimental Research, 2009)
Ethanol induces similar behavioral responses in mammals and the fruit fly, Drosophila melanogaster. By coupling assays for ethanol-related behavior to the genetic tools available in flies, a number of genes have been identified that influence physiological responses to ethanol. To enhance the utility of the Drosophila model for investigating genes involved in ethanol-related behavior, we explored the value of an assay that measures the sedative effects of ethanol on negative geotaxis, an evoked locomotor response.We established eRING (ethanol Rapid Iterative Negative Geotaxis) as an assay for quantitating the sedative effects of ethanol on negative geotaxis (i.e., startle-induced climbing). We validated the assay by assessing acute sensitivity to ethanol and rapid ethanol tolerance in several different control strains and in flies with mutations known to disrupt these behaviors. We also used eRING in a candidate screen to identify mutants with altered ethanol-related behaviors.Negative geotaxis measured in eRING assays was dose-dependently impaired by ethanol exposure. Flies developed tolerance to the intoxicating effects of ethanol when tested during a second exposure. Ethanol sensitivity and rapid ethanol tolerance varied across 4 control strains, but internal ethanol concentrations were indistinguishable in the 4 strains during a first and second challenge with ethanol. Ethanol sensitivity and rapid ethanol tolerance, respectively, were altered in flies with mutations in amnesiac and hangover, genes known to influence these traits. Additionally, mutations in the beta integrin gene myospheroid and the alpha integrin gene scab increased the initial sensitivity to ethanol and enhanced the development of rapid ethanol tolerance without altering internal ethanol concentrations.The eRING assay is suitable for investigating genetic mechanisms that influence ethanol sensitivity and rapid ethanol tolerance. Ethanol sensitivity and rapid ethanol tolerance depend on the function of alpha and beta integrins in flies.